More recent, better designed studies have weakened links between antidiabetes medications and cancer risk. Issue 2 (3rd January 2020) - Dankner, R.; Roth, J.
Abstract: Background: An increasing number of studies have investigated associations of antidiabetes medications with cancer risk. Antidiabetes medications are classified by their mechanisms of action on tissues and organs. They potentially act as both causative and confounding factors in the temporal association of diabetes and cancer. Aim: To present the current evidence regarding both the carcinogenic and anti‐carcinogenic effects of antidiabetes medications on cancer in humans. Methods: A review of the scientific literature. Results: The most conclusive evidence shown of an association of antidiabetes medication with a specific cancer was for that of the thiazolidinedione pioglitazone with bladder cancer. Currently, there is inconclusive evidence regarding a possible association of incretin therapies, drugs of the dipeptidyl peptidase‐4 inhibitor class, with the risk of pancreatic cancer. Insulin, sulfonylureas, metformin and sodium‐glucose co‐transporter‐2 inhibitors appear not to be associated with increased risk of any cancer. Sparse evidence suggests possible protective effects against cancer incidence of metformin, sulfonylureas, thiazolidinediones, incretin‐based drugs and sodium‐glucose co‐transporter‐2 inhibitors. Conclusion: The conflicting evidence regarding associations of antidiabetes medications with cancer risk is apparently attributable to both methodological issues and to the complexity of the subject. More recent and better‐designed studies have weakened the evidence for links between antidiabetes medications and cancer risk. What's new?: As diabetes is recognized for its association with cancer risk, the study of associations of antidiabetes medications and cancer risk has become a clinical and research focus in recent years. Conflicting observational evidence has associated some antidiabetes medications with increased cancer risk and other antidiabetes medications with decreased cancer risk. Secondary analyses of randomized controlled trials and most observational studies that have addressed time‐related biases do not support associations of exposure to antidiabetes medications with cancer risk. Still lacking are well‐designed observational studies with appropriate definitions of exposure and inclusion criteria that control for sample selection so as to account for bias, confounding factors and missing data, and with suitable censoring methods and outcomes, to establish the associations of antidiabetes medications and site‐specific cancer risk.